Measurement of the eco-efficiency of small business in the supply chain oil and gas, applying the taxonomy CE7 - Bezerra, Paulo Ricardo Cosme; Vieira, Marcela Marques; Rezende, Júlio Francisco Dantas de (Acta Scientiarum. Technology, 2019)
This article intends to contribute to studies concerning environmental sustainability in the oil and gas industry by measuring the eco-efficiency of small business in the supply chain of oil and gas in Brazil. Eco-efficiency is an environmental management strategy that aims to reduce resource consumption, reduce the impact on nature and provide customers with quality products and services. For its measurement, the methodology called `CE7´ taxonomy was used, an acronym referring to the `seven competences of eco-efficiency´ that adapted the environmental strategies will show the level of eco-efficiency of the enterprises. The field research adopts as object of study forty-four companies of the productive chain of oil and gas Potiguar. Data were collected from August to October 2016, using the survey method. It was evidenced the absence of eco-efficient enterprises in the production chain and that the best level of delivery occurred for two companies that were diagnosed as `almost eco-efficient´. The environmental strategies that promote eco-efficiency are energy efficiency, solid waste management plan, environmental care in supplier selection and environmental licensing. Eco-efficiency is not an institutionalized management practice in the reality of this productive chain.